Stratification of Risk Factors of Lung Cancer-Associated Venous Thromboembolism and Determining the Critical Point for Preemptive Intervention: A Systematic Review With Meta-analysis - Theresa Nwagha; Martins Nweke (Clinical Medicine Insights: Oncology, 2023)
Background: Several biomarkers or risk factors have been identified and several prediction models exist. The major limitations inherent in these models include cost-ineffectiveness and lack of systematic stratification of risk factors resulting in the inclusion of clinically insignificant biomarkers in the models. This review aimed to systematically stratify the risk factors of lung cancer-associated venous thromboembolism (VTE) and determine the critical point for preemptive intervention. Methods: This systematic review was structured as per the Preferred Reporting Item for Systematic Reviews and Meta-analyses. We searched MEDLINE, PubMed, Cochrane Library, CINAHL, Academic Search Complete, and PsycINFO from the onset to June 2022. We included studies that reported the risk factors of lung cancer-associated VTE and corresponding risk estimates, irrespective of treatment status but studies were excluded if patients were on anti-VTE medications. We employed random effects models of meta-analysis and computed risk stability index and risk weight (Rw) to achieve the review objectives. The review protocol is registered with PROSPERO (CRD42022336476). Results: The clinically significant risk factors of VTE in lung cancer patients were D-dimer (odds ratio [OR] = 5.510, 95% CI = 2.6-11.7; Rw = 5.0), albumin (OR = 2.2, 95% CI = 1.0-4.8; Rw = 1.79), leukocyte (OR = 2.48, 95% CI = 1.9-3.2; Rw = 1.77), histological type (OR = 1.69 , 95% CI = 1.2-2.4; Rw = 1.3), age (OR = 1.56; Rw = 0.99), and hemoglobin (OR = 1.85, 95% CI = 1.3-2.6; Rw = 0.92). Based on the distribution of Rw across risk factors, the critical point (upper third of the upper quartile class) was 4.5 and may mark the point at which preemptive intervention should be commenced. Conclusions: Targeted screening for VTE in lung cancer patients could be patient-specific and should be based on a combination of the most significant risk factors required to meet the critical point, provided that such a combination is affordable as illustrated in the ALBAH model. Registration: The review protocol is registered with PROSPERO (ID: CRD42022336476).